Piezoelectric and thermophysical performances of La3+ and Ir4+ co-doped Ba0.95Ca0.05Ti0.94Zr0.06O3 ceramics. Issue 10 (July 2019) - Tian, Yongshang; Cao, Lijia; Qin, Panpan; Sun, Shujie; Gong, Yansheng; Ji, Xiang; Jing, Qiangshan
Abstract: Rare earth element-doped piezoelectric ceramics exhibit excellent electrical properties. Platinum group elements can render them catalytically active and conductive. In this study, lead-free Ba0.95 Ca0.05 Ti0.94 Zr0.06 O3 piezoelectric ceramics doped with 0.12% lanthanum and iridium (varying contents, x ) were sintered at 1260 °C. The thermal expansion coefficients and fracture strengths of these ceramics were affected by their strains and structural defects. With an increase in x, the diffuse phase transition weakened first and then accelerated (with further increase in x ( > 0.75%)). The best ferroelectric properties were obtained at 400 ms and 25 kV/cm. The effects of the phase, structural defects, and internal stress on the electrical properties of the ceramics were systematically investigated. Relations of electrical properties, mechanical strength, and thermophysical performances were originally researched. In addition, the electrical properties (piezoelectric constants, ∼270 pC/N; mechanical quality factors, ∼ 70) and thermophysical performances (thermal expansion coefficient, ∼1.2 × 10 −5  K −1 ) of the ceramics were found to be suitable for practical applications.